2008
DOI: 10.1111/j.1600-0609.2008.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of Polycomb, Hox and Meis genes in patients with acute myeloid leukaemia

Abstract: The Polycomb group (PcG) of genes is important for differentiation and cell-cycle regulation and is aberrantly expressed in several cancers. To analyse the role of deregulated PcG genes in acute myeloid leukaemia (AML), we determined by RQ-PCR the expression of the PcG genes BMI-1, MEL18, SCML2, YY1 and EZH2, and the downstream PcG targets HOXA4, HOXA9 and MEIS1 in diagnostic bone marrow samples from 126 AML patients. There was a general overexpression of the genes in AML patients compared to 20 healthy donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
70
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 48 publications
11
70
2
1
Order By: Relevance
“…Overexpression of EZH2 has been reported in patients with high-risk MDS, MDS-derived AML, and AML, particularly in patients with complex karyotypes. 15,35 The inhibitory effect of the knockdown of EZH2 and the similar effect of DZNep on AML cells further supports the oncogenic function of EZH2 in AML. 21,22,36 In the present study, we have shown that deletion of Ezh2 compromises the progression of AML severely by promoting the differentiation of AML cells.…”
Section: Discussionmentioning
confidence: 60%
“…Overexpression of EZH2 has been reported in patients with high-risk MDS, MDS-derived AML, and AML, particularly in patients with complex karyotypes. 15,35 The inhibitory effect of the knockdown of EZH2 and the similar effect of DZNep on AML cells further supports the oncogenic function of EZH2 in AML. 21,22,36 In the present study, we have shown that deletion of Ezh2 compromises the progression of AML severely by promoting the differentiation of AML cells.…”
Section: Discussionmentioning
confidence: 60%
“…These findings support earlier reports that point to a role of HOX and Polycomb as target genes in leukemia. 35 In addition, another major objective of our study was to determine whether patterns of DNA methylation could be used to improve patient prognostication. Using a semisupervised approach, 31 we were able to build a predictive model based on quantitative methylation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…23 The authors, using different approaches, demonstrated that YY1 is overexpressed in osteosarcoma cell lines and tissues compared to normal osteoblastic cells with a predominant localization in the nucleus. 23 High levels of YY1 were observed in non-solid tumors, including myeloid leukemia (AML), 24 Hodgkin lymphoma (HD) 25 and Non-Hodgkin lymphoma (NHL), 26,27 when compared to normal samples. Sakhinia et al 26 showed that YY1 was upregulated in follicular lymphoma (FL) and in diffuse large B-cell lymphoma (DLBCL).…”
Section: Implication Of Yin Yang 1 In Response To Therapeutic-inducedmentioning
confidence: 99%